Early Surgical Treatment Options for Anterior Cruciate Ligament Injury - Hušek, Filip; Mizera, Roman; Čapek, Lukáš; Horák, Zdeněk (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2025)
Anterior cruciate ligament (ACL) is one of the most commonly injured structures in distortion injuries of the knee joint. Currently, there is no consensus among the professional community regarding the basic principles and timing of ACL injury management. An analysis of several retrospective studies from the 2008-2023 period provides information on ACL preservation procedures and a comparison of these results with those of ACL reconstruction surgery using a graft. The most comprehensive information was provided by a large meta-analysis conducted by Van der List et al. in 2019, which compared 1101 patients from 13 studies who had undergone an ACL preservation surgery. Wilson et al. carried out a retrospective study of patients who underwent ACL repair with InternalBrace (Arthrex© implant system) ligament augmentation. In their meta-analysis, Van der List et al. reported the failure rate of 7-11% and the functional outcome score > 85% of maximum scores in the scoring systems used (Lysholm, KOOS, IKDC score) for the preservation procedures. Wilson et al. in their retrospective study reported the failure rate of 10.4% and the functional outcome > 87% of maximum scores in the scoring systems used. These values are consistent with similar outcomes reported in patients undergoing ACL reconstruction surgery using a graft. According to the available literature, the primary ACL refixation with InternalBrace augmentation for proximal ruptures appears to be a safe technique with satisfactory outcomes when properly timed and indicated. In acute proximal ruptures, this technique should be considered as an alternative to ACL reconstruction using a graft, with potential benefits of preserving the original tissue and proprioception of the ligament. A prospective randomized study which would compare these two surgical techniques is still lacking in the literature.
Keywords: výsledek terapie; proximal rupture; Anterior Cruciate Ligament Reconstruction; rekonstrukce předního zkříženého vazu; ACL; InternalBrace.; primary repair; retrospektivní studie; Humans; Anterior Cruciate Ligament Injuries; Retrospective Studies; Treatment Outcome; Anterior Cruciate Ligament; lidé; ligamentum cruciatum anterius; poranění předního zkříženého vazu